Preconcentration of Chromium(VI) at Trace Levels Using Acid Alumina Resin with Column Method - Aman Sentosa Panggabean; Subur P Pasaribu; Bohari Bohari; Nurhasanah Nurhasanah (Universitas Gadjah Mada, 2014)
Trace analysis of Chromium(VI) ions using acid alumina resin as a filler material column in preconcentration system by off-line method has been carried out. Alumina resin was activated with H2SO4 at pH 1 before being filled to the column. This research showed retention capacity of alumina acid resin was 3.955 mg Cr(VI)/g resin. The analytical performance of this method is good, shown with the limit of detection value was 3.648 µg/L. The reproducibility of this method shown as percentage of coefficient variance was 2.06%. Acid alumina used as resin filler column can increase the signal up to 15.36 times for direct Cr(VI) ions measurement. The accuracy of this method is very good with the recovery percentage value > 95%, shown the matrices of water samples didn’t effect the results of measurements and this method was capable to analyze Cr(VI) ions in water samples at the trace levels.